PENGGAMBARAN MASKULINITAS PEREMPUAN DALAM FILM ALIENS : KAJIAN SEMIOTIKA - novita indah permata sari (Universitas Bunda Mulia, 2021)
This thesis is entitled “Penggambaran Maskulinitas Perempuan dalam Film Aliens: Kajian Semiotika”. The thesis is aimed to describe the signs that appear in the film Aliens, and the type of female masculinity attributes in the film Aliens. The object of this thesis is film Aliens published in 1986 produced by James Cameron. The method that is used in this thesis is a descriptive analytic method. The writer uses the semiotic theory of Saussure (1916) and some other supported theories, such as masculinity theory of Sanders (1996), gender theory of Andersson (2008), masculinity attributes theory of Visser (2002), and dominant nonverbal sign theory of Givens (2002). The result of this research shows that the signs which shows the image of female masculinity are verbal, visual, and nonverbal signs, i.e, gestures, texts and symbols, and the types of female masculinity attributes that appear are career oriented, strong, dominant, interested in technology and rational.